The “autonomy” of developing countries in the Olympic Movement: Assessing the fate of sports governance transplants in the Global South - García, Borja; Meier, Henk Erik (Frontiers in Sports and Active Living, 2022)
Introduction The International Olympic Committee (IOC) imposes very specific ideas on sports governance, more precisely on sports autonomy, on countries joining the Olympic Movement. Given that the idea of sports autonomy originated in the Global North, this article introduces the concept of governance transplants to evaluate the impact that being part of the Olympic Movement has on domestic sports governance in Global South developing countries. The article explores the extent to which the IOC is successful in implementing the norms and regulations on sports autonomy as a governance transplant at the national level in countries from the Global South that are part of the Olympic Movement. Methods The article employs a comparative qualitative case study research design that explores the relations of the IOC, National Olympic Committees (NOCs), and national governments in Botswana, Guatemala and Sri Lanka. Research relies on a mix of document analyses and expert semi-structured interviews conducted during field trips to those countries. Interviews were transcribed and analyzed by means of thematic analysis. The analyses focus on domestic policies and contexts, formal and institutional compliance with sports autonomy, provision of public funding, and participation in national sport policy-making. Results and discussion Findings suggest that national structures and legacies have an impact on the way in which the autonomy of sport, as the governance transplant, is translated in those three countries. Although national governments enjoy some agency in “translating” governance transplants, results also suggest that misfits and tensions persist between governmental and sport stakeholders at the national and international level. Such misfits might force the IOC, as a private transnational regulator, to adopt a more pragmatic view on the enforcing of its governance transplants. The results are of relevance to existing discussions on global sports governance and debates as to whether the countries in the Global North might be able to impose their views and their governance transplants if the Global South gets a greater say in transnational sports governance.